Using routinely collected laboratory and health administrative data to assess influenza vaccine effectiveness: introducing the Flu and Other Respiratory Viruses Research (FOREVER) Cohort. (2018) - Kwong, Jeff; Buchan, Sarah; Chung, Hannah; Campitelli, Michael; Schwartz, Kevin; Crowcroft, Natasha; Jackson, Michael; Karnauchow, Timothy; Katz, Kevin; McGeer, Allison; McNally, Dayre; Richardson, David; et al.
No abstract available